2013
DOI: 10.1007/s13555-013-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Cellulite and Focused Extracorporeal Shockwave Therapy for Non-Invasive Body Contouring: a Randomized Trial

Abstract: IntroductionFocused extracorporeal shockwave therapy (ESWT) has been demonstrated to improve wound healing and skin regeneration such as in burn wounds and scars. We hypothesized that the combination of focused ESWT and a daily gluteal muscle strength program is superior to SHAM-ESWT and gluteal muscle strength training in moderate to severe cellulite.MethodsThis was a single-center, double-blinded, randomized-controlled trial. For allocation of participants, a 1:1 ratio randomization was performed using opaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 19 publications
0
46
0
3
Order By: Relevance
“…In addition, the procedure has been used for curing lesions and wounds. Nowadays, the device is being used for body contouring and treating cellulite (66, 67). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the procedure has been used for curing lesions and wounds. Nowadays, the device is being used for body contouring and treating cellulite (66, 67). …”
Section: Resultsmentioning
confidence: 99%
“…Daily gluteal strength trainings were prescribed for both groups. The results showed significant improvement in skin appearance and cellulite severity scale, but no effect on thigh circumference was reported (67). …”
Section: Resultsmentioning
confidence: 99%
“…29,40 Some ESWT devices generate pressure waves that fulfill the characteristics set out by this physical definition of real shock waves, whereas others do not 29,40,41. Among those ESWT devices that do not produce real shock waves is the electromagnetic Duolith ® device (Storz Medical)41 that has recently been introduced into ESWT for cellulite 16. Another device that was used in several studies for treating cellulite is the D-Actor ® 200 (Storz Medical) 15,17,22.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated improvement in cellulite appearance or grade after 6–8 weekly sessions 42–44…”
Section: Treatment Optionsmentioning
confidence: 99%